Wealth Distributions of Migrant and Australian-Born Households - Belkar, R (My University, 2005)
Wealth is an important measure of overall economic well-being, and influences migrants’ ability to integrate into their new country. Using data from the 2002 HILDA survey, this study explores the disparity between the wealth distributions of Australian and foreign-born households. Using quantile regressions, the results reveal that immigrants accumulate less wealth than their Australian-born counterparts and that the gap grows throughout the distribution. Further analysis reveals that migrants are able to catch up to their native born counterparts not only through greater time in Australia, but also through human capital accumulation, part of which may be achieved in Australia.
University of New South Wales Working Paper
Keywords: Finance; Culture -- Immigrants; Finance -- Wealth; Culture; Income, wealth and finances; Culture and language; Culture and identity; Culture, identity and language; Income, wealth and finances